Deconstructing 2022 Philippine election discourses a multimodal discourse analysis and audience reception study of Facebook political satirical news - Dela Peña, Patricia Emerie B.; Mansos, Gizelle M.; Paragas, Fernando dlC (Quezon City College of Mass Communication, University of the Philippines, 2023)
In this qualitative research. we employ multimodal critical discourse analysis, audience reception theory, and cultural studies to investigate the impact of political satirical news posts on Facehook pages on the discourse and opinions of Filipino youths regarding socio-political issues in the aftermath of the 2022 Philippine elections. We examine 30 satirical news posts from three satire pages for their cultural references, language use, sensationalism, and personal attacks, all of which aim to engage specific groups and elicit emotional responses. Furthermore, we explore the use of rhetorical tropes. like hyperbole and metonymy, to critique political figures and explicate societal issues. To gain insight into the reception and interpretation of these posts by Filipino youths, we interviewed 10 informants who held diverse political stances and were exposed to satirical news posts during the post-election period of 2022. Our findings 'Hight the value of satire in stimulating dialogue and critical analysis, while emphasizing the need for caution and discernment due to the presence of misinformation. Our research recognizes satirical news pages as alternative platforms in a context of declining trust in mainstream media, contributing to the construction of social and political commentaries on Facebook.
Vita.
Thesis
Includes bibliographical references(pages 192-202) and appendices (pages 203-216).
Keywords: Satire -- Politics and government .; Online social networks -- Philippines; Political campaigns -- Philippines